2012
DOI: 10.3126/sw.v10i10.6870
|View full text |Cite
|
Sign up to set email alerts
|

Aroma profile of Eucalyptus globulus: collected from North West Karnataka, India

Abstract: Abstract:The chemical composition of the essential oil of the leaves of Eucalyptus globulus (Myrtaceae) grown in North West Karnataka, has been analyzed by GC and GC/MS. Forty-eight constituents were identified, accounting 97.93% of the total oil. The major compounds were á-phellandrene (40.31%), á-pinene (13.71%), â-pinene (13.31%), ã-terpinene (9.61%) and 1,8-cineol (4.96%). The oil was rich in monoterpene hydrocarbons (81.14%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
1
6
0
Order By: Relevance
“…The oil yield of E. camaldulensis from Jerusalem was 0.5% (Chalchat et al, 2000) and significantly higher oil yield was reported for E. camaldulensis from Taiwan: 2.3-3.0% with respect to different seasons (Shieh, 1996). Similar EOs yield (0.77-2.53%) has been reported for E. globulus, as one of the economically important plants for essential oil production (Joshi, 2012;Selvakumar et al, 2012;Harkat-Madouri et al, 2015). The reported essential oil yield for other Eucalyptus species is slightly higher, ranging from 1.2% to 3% (w/w): the highest yield was obtained from E. cinerea F. (Sebei et al, 2015).…”
Section: Eucalyptus Camaldulensis Essential Oil Chemical Compositionsupporting
confidence: 75%
“…The oil yield of E. camaldulensis from Jerusalem was 0.5% (Chalchat et al, 2000) and significantly higher oil yield was reported for E. camaldulensis from Taiwan: 2.3-3.0% with respect to different seasons (Shieh, 1996). Similar EOs yield (0.77-2.53%) has been reported for E. globulus, as one of the economically important plants for essential oil production (Joshi, 2012;Selvakumar et al, 2012;Harkat-Madouri et al, 2015). The reported essential oil yield for other Eucalyptus species is slightly higher, ranging from 1.2% to 3% (w/w): the highest yield was obtained from E. cinerea F. (Sebei et al, 2015).…”
Section: Eucalyptus Camaldulensis Essential Oil Chemical Compositionsupporting
confidence: 75%
“…Although E. globulus is not highly invasive in the non‐native regions included in our study (Becerra, ; Cal‐IPC, ; Kirkpatrick, ), Eucalyptus species are important forestry species, with thousands of hectares planted around the world (Boyd, ; Dixit et al, ; Joshi, ; Rejmánek et al, ). Thus, our results are also relevant to the conservation of biodiversity within plantations.…”
Section: Discussionmentioning
confidence: 95%
“…is one of the most common (Boyd, ). This species has been introduced around the world for wood products and horticulture (Becerra, ; Boyd, ; Dixit, Rohilla, & Singh, ; Joshi, ; Rejmánek, Richardson, Higgins, Pitcairn, & Grotkopp, ). Eucalyptus globulus does not commonly spread into native vegetation and thus is not usually considered a strongly “invasive” species (but see Boyd, ; Becerra, ).…”
Section: Introductionmentioning
confidence: 99%
“…In India there are number of Eucalptus species available such as E. tereticornis, E. grandis, E. citriodora, E. globulus, and E. camaldulensis. There are various studies available on chemical composition and antimicrobial activity of essential oil of Eucalyptus of Indian origin 19,20 but to the best of my knowledge, no report is available on the chemical constituents of Eucalyptus globulus leave essential oil grown in Dehradun, India.…”
Section: Introductionmentioning
confidence: 99%